PENEGAKAN HUKUM TINDAK PIDANA PENGGELAPAN PERSPEKTIF HUKUM POSITIF DAN HUKUM ISLAM - Azzahro, Fatima; Rosyadi, Moh. Imron; zahro, Fatima (Universitas Islam Negeri Raden Fatah Palembang, 2024)
The crime of embezzlement is the act of taking or receiving property belonging to another person without the owner's consent, which not only violates the law but also has a negative impact on the economy and society. This crime is regulated in Articles 372–377 of the Criminal Code (KUHP), which is included in the category of criminal offenses in the Second Book on Crime. Embezzlement is a type of crime that often occurs in various fields and is committed by perpetrators from various levels of society, both from the lower and upper classes. This criminal act generally begins with the trust given to someone, but this trust is betrayed due to weak integrity and honesty. In Islamic law, embezzlement is similar to the concept of ghulul, although the regulations regarding this criminal act are not explicitly mentioned in the Koran and Hadith. This research aims to examine the crime of embezzlement from the perspective of positive law and Islamic law, using normative data as analysis material. The results of this research provide an understanding of the law enforcement mechanisms related to embezzlement from both perspectives. Apart from that, it is hoped that this study can contribute to efforts to prevent embezzlement in society by instilling the value of honesty and strengthening the applicable legal system.